Covalently Bonded 2D/0D g‐C3N4/MoS2 Nanocomposites for Enhanced Tribological Properties in Oil. Issue 7 (16th February 2021) - Min, Chunying; Yang, Yuzi; Liang, Hongyu; He, Zengbao; Zhu, Jinfeng; Li, Qiuying
Abstract: In current work, by an ordinary one‐step hydrothermal strategy, the covalently bonded graphitic carbon nitride/molybdenum disulfide (g‐C3 N4 /MoS2 ) nanocomposites were successfully synthesized. SEM, TEM analyses evidenced the well distribution of MoS2 nanoparticles on g‐C3 N4 . The covalent bond (C−S bond) between two‐dimensional (2D) g‐C3 N4 and zero‐dimensional (0D) MoS2 were confirmed by FTIR and XRD. Furthermore, the average friction coefficient and wear rate of g‐C3 N4 /MoS2 nanocomposites at 0.20 wt % concentration could separately reach up to 27.86 % and 70.87 % reduction by comparing pure oil, benefiting from synergistic lubrication of g‐C3 N4 nanosheets plus spherical MoS2 . In the work, novel guidance will be provided for the potential application of multi‐dimensional g‐C3 N4 ‐based nanocomposites in lubricating field. Abstract : We synthesized covalently bonded 2D/0D g‐C3 N4 /MoS2 Nanocomposites by an ordinary one‐step hydrothermal strategy and studied their tribological nature as oil‐based lubricant additives. Compared with the pure oil, the average friction coefficient and wear rate had been decreased by 27.86 % and 70.87 % after taking g‐C3 N4 /MoS2 nanocomposites as additives at 0.20 wt % concentration. This work will provide guidance for multi‐dimensional g‐C3 N4 ‐based nanocomposites in tribological field.